Pengembangan Inovasi Daerah Berkelanjutan Menuju Kabupaten Gemilang Tangerang: Studi di Kabupaten Tangerang - Ramadhan, Arif; Syah, Ardy Firman; Plamonia, Nicco; Andreani, Selfy; Yohanitas, Witra Apdhi (Jurnal Bina Praja, 2023)
The development of sustainable regional innovation is a step taken in realizing Tangerang Gemilang Regency. Tangerang Gemilang branding introduces regional potentials, such as tourism, industry, agriculture, and culture. Through sustainable innovation, regional development programs develop the superior potentials in the region more efficiently and effectively to increase regional competitiveness and positively impact society. This research aims to identify sustainable innovations that have been implemented by the Tangerang Regency Government, as well as to analyze the factors that influence the successful development of these innovations. The novelty of the research lies in the discussion of the implementation of regional innovations in the Tangerang Regency that have been carried out sustainably. The research discusses various aspects of sustainable regional innovations, including tourism, technology, infrastructure, and community participation. The research has an explanatory nature with a qualitative approach and a single case study where data is collected through in-depth interviews, observation, document analysis, and descriptive data processing. Then the independent variables (brand awareness, product innovation, number of new products, regional identity) and dependent variables (tourist attraction, industry, trade) were analyzed. The research found that implementing sustainable regional innovation to realize the branding of the Tangerang Gemilang district has been stated in the 2019-2014 RPJMD. Realizing Tangerang Gemilang with a sustainable innovation ecosystem requires a participatory and collaborative approach. Collaboration makes the ecosystem develop and have an impact. The importance of the innovation ecosystem is to reduce progressive programs that are often stopped when there is a change of regional head or mutation of regional apparatus leaders. Sustainability requires technical and policy innovation as well as a philosophical foundation in the form of city branding with careful planning. Tangerang Regency has proven this through policy preparation, mentoring and comprehensive evaluation of innovative programs to realize Tangerang Gemilang.